Pericarditis With Effusion in Children - A. Samik Wahab, A. Samik Wahab (Universitas Gadjah Mada, 1974)
Two cases of pericarditis with effusion admitted to the Department of Child Health, Gadjah Mada University Hospital were presented. The suspicion was based on the presence of pericardial friction rub for the first case, and the presence of cardiac enlargement and liquid line (on X-ray) for the second case. Pericardiocentesis was performed to confirm the diagnosis and for treatment.An accurate etiological diagnosis could not be made due to lack of laboratory facilities. The treatment was based on clinical and pathological findings